Strategi Penetapan Harga Jual UMKM : Perbandingan Metode Full Costing Dan Variable Costing Dalam Menunjang Keberlangsungan Usaha (Studi Kasus Pelipur Lapar Sidoarjo) - Ningrum, Dewi Agustya; Persada, Cipta Damai (IQTISHADequity jurnal MANAJEMEN, 2025)
This research discusses the importance of cost calculation in determining appropriate selling prices for Micro, Small, and Medium Enterprises (MSMEs), with a particular focus on Pelipur Lapar Sidoarjo. MSMEs play a vital role in Indonesia’s economy, contributing significantly to economic development and employment creation. In the pricing process, the full costing and variable costing methods are commonly em-ployed to calculate the Cost of Goods Sold (COGS). Full costing encompasses all variable and fixed costs comprehensively, resulting in a higher COGS and a more detailed depiction of expenses. Conversely, variable costing considers only the direct variable costs associated with the production process, making it simpler and more suitable for short-term decision-making. This study adopts a qualitative approach, collecting data through interviews and direct field observations, and analyzes the COGS based on both methods. The results indicate that the COGS calculated via full costing is IDR 14,000 per portion, while the variable costing approach yields IDR 13,000 per portion. The selling prices determined using the cost-plus pricing ap-proach also differ, at IDR 22,000 and IDR 20,000 per portion, respectively. These findings confirm that employing the full costing method can assist MSMEs in setting more accurate and profitable prices, thereby supporting business sustainability. It is recommended that MSME actors perform comprehensive and precise cost calculations as a basis for pricing decisions to enhance competitiveness and contribute more effec-tively to the national economy.